Establishing the Character of Love for the Country of Students in Growing an Attitude of Nationalism - Ahmadin Ahmadin (STKIP Taman Siswa Bima, 2023)
The attitude of nationalism in schools is decreasing, and this is evidenced by various problems that occur in the school environment. The character of loving the motherland needs to be instilled in students so that they have a strong attitude of nationalism and love the local culture more, especially being able to appreciate the services of the heroes who have fought for Indonesian independence. Civics teachers in the formation of the character of loving the motherland and the inhibiting and supporting factors in the formation of the character of loving the motherland to foster students' nationalism. The approach in this research is qualitative with descriptive type. Data collection techniques using interviews (interviews), observation and documentation studies. The results showed that (1) the formation of the character of loving the motherland to foster an attitude of nationalism in students, namely carrying out routine flag ceremonies and extracurricular activities by singing the national anthem; (2) the role of the Civics teacher in forming the character of loving the motherland to foster students' nationalism, namely the teacher as the central pillar for students in learning and as an example or role model in character building. (3) In forming the character of loving the motherland, guidance is needed, and it takes time as well as the patience of the teacher and parents so that students will be motivated to have the expected attitude.